Relationship Between Father And Children After Divorce: Integrative Literature Review - Oliveira, Joyce Lúcia Abreu Pereira (2018)
The continuity of the relationship between the father and the children after the divorce favors the development of the child and the family. This study aimed to present an integrative review of empirical research literature on the relationship between fathers and children after divorce/marital separation. The results suggests that: there are factors that favor and factors that hinder the relationship between fathers and children after divorce; this relationship exerts influence on the development of children and adolescents; separated-father parenting is marked by specific characteristics; and psychological interventions with divorced fathers are indicated to improve the functioning of binuclear families. This subject is highly relevant for the training of professionals in the health, education and legal fields, since it is a multifaceted phenomenon, complex and relevant for the development of children and family.